Italian lessons - Pezzelli, Peter (Kensington Books, 2007)
Fresh out of college, Carter returns to Rhode Island and plans to go to Italy to pursue the woman of his dreams, but needs to learn Italian. An apparent mismatch between mentor and student soon blossoms into something deeper.